2011
DOI: 10.1111/j.1651-2227.2011.02241.x
|View full text |Cite
|
Sign up to set email alerts
|

CD4+CD25high Treg cells in peripheral blood during remission and exacerbation of allergic asthma in children

Abstract: CD4+CD25(high) T-cell proportion in the peripheral blood of total CD4+T cells is not reduced in children with allergic IgE-mediated asthma and does not differ between disease remission and exacerbation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 26 publications
0
11
1
Order By: Relevance
“…Many studies addressed predictors of remission or persistence of asthma from early childhood through adulthood (23)(24)(25)(26). Immunoregulatory parameters related to the outcome of childhood asthma have been widely discussed, however are not yet well established (4,7,10,19,27). Speci c observations in the present study, regarding immunology parameters, were surprising.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…Many studies addressed predictors of remission or persistence of asthma from early childhood through adulthood (23)(24)(25)(26). Immunoregulatory parameters related to the outcome of childhood asthma have been widely discussed, however are not yet well established (4,7,10,19,27). Speci c observations in the present study, regarding immunology parameters, were surprising.…”
Section: Discussioncontrasting
confidence: 57%
“…A wide range of cell types and suppressive molecules are involved in induction and maintenance of tolerance. The forkhead transcription factor (Foxp3) expression in regulatory T cells (Tregs) plays a crucial role in maintaining immunological tolerance (4,5). The IL-2 receptor (CD25) and transferrin receptor (CD71) are activation markers of T and B cells, and their increased expression might re ect an increased activation state (3,6).…”
Section: Introductionmentioning
confidence: 99%
“…hi regulatory cells in atopic asthmatic children, both during remission and exacerbation [32]. They observed no significant correlation of CD4 +…”
Section: Cd25mentioning
confidence: 87%
“…Some authors have reported lower levels of Treg cells in asthma patients [31]. Pumputiene et al have recently studied CD4 + CD25 hi regulatory cells in atopic asthmatic children, both during remission and exacerbation [32]. They observed no significant correlation of CD4 + CD25 hi T cell percentages.…”
Section: Whole Blood Culturesmentioning
confidence: 97%
“…Objective quantitative data on children's independent mobility and physical activity are collected using current best practice epidemiological approaches. Advancing on earlier research [67,68], objective measurement of children's independently mobile trips have been quantified in detail, drawing from travel diary, GPS, and accelerometer data. Built environmental features have been objectively quantified utilizing a variety of tools, providing a detailed quantification of this factor in relation to children's activity and mobility.…”
Section: Discussionmentioning
confidence: 99%